2009
DOI: 10.1037/a0012944
|View full text |Cite
|
Sign up to set email alerts
|

Syllabic priming in lexical decision and naming tasks: The syllable congruency effect re-examined in French.

Abstract: This study investigated the role of the syllable in visual recognition of French words. The syllable congruency procedure was combined with masked priming in the lexical-decision task (Experiments 1 and 3) and the naming task (Experiment 2). Target words were preceded by a nonword prime sharing the first three letters that either corresponded to the syllable (congruent condition), or not (incongruent condition). When primes were displayed for 67 ms, similar results were found in both the lexical decision and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
40
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 47 publications
(149 reference statements)
8
40
2
Order By: Relevance
“…Beyond the necessities of this specific experimental situation per se, the syllabic structure is a variable which has received little consideration to date in skilled reading. However, some data indicated that words beginning with a consonant-vowel-consonant first syllable were processed longer than words beginning with a consonant-vowel first syllable (Chetail and Mathey 2009a), and that syllable congruency effects were more reliable for words beginning with a consonant-vowel first syllable (Alvarez et al 2004), thus suggesting the need to take this variable into account. In the same vein, little information is provided about the establishment of syllable boundaries when selecting words for experiments on syllables.…”
Section: The Syllabic Issue In Readingmentioning
confidence: 98%
See 4 more Smart Citations
“…Beyond the necessities of this specific experimental situation per se, the syllabic structure is a variable which has received little consideration to date in skilled reading. However, some data indicated that words beginning with a consonant-vowel-consonant first syllable were processed longer than words beginning with a consonant-vowel first syllable (Chetail and Mathey 2009a), and that syllable congruency effects were more reliable for words beginning with a consonant-vowel first syllable (Alvarez et al 2004), thus suggesting the need to take this variable into account. In the same vein, little information is provided about the establishment of syllable boundaries when selecting words for experiments on syllables.…”
Section: The Syllabic Issue In Readingmentioning
confidence: 98%
“…Syllable congruency effects have also been found in the naming task, though the data are more contrasted. Some studies reported facilitatory syllable congruency effects (Chetail and Mathey 2009a;Ferrand et al 1996 in French;Ferrand et al 1997, in English) while others did not (e.g., Brand et al 2003;in French;Schiller 1998, in Dutch;Schiller 2000, in English). In particular, segmental priming effects were found rather than syllable congruency effects.…”
Section: The Syllabic Issue In Readingmentioning
confidence: 99%
See 3 more Smart Citations